2014
DOI: 10.1164/rccm.201311-2012oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sleep Apnea and Continuous Positive Airway Pressure Therapy in the Incidence of Stroke or Coronary Heart Disease in Women

Abstract: In women, untreated OSA is associated with increased incidence of serious cardiovascular outcomes, particularly incident stroke. Adequate CPAP treatment seems to reduce this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
111
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 31 publications
4
111
0
1
Order By: Relevance
“…The effectiveness of CPAP therapy in improving clinical symptoms, quality of life and potential consequences associated with OSA is strongly related to compliance (7)(8)(9)(10); nevertheless, the predictors of adherence to this therapy are still not well known.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of CPAP therapy in improving clinical symptoms, quality of life and potential consequences associated with OSA is strongly related to compliance (7)(8)(9)(10); nevertheless, the predictors of adherence to this therapy are still not well known.…”
Section: Introductionmentioning
confidence: 99%
“…The first-line treatment for patients presenting OSA is continuous positive airway pressure (CPAP) therapy [9], which significantly ameliorates symptoms as well as its cardiovascular consequences [10][11][12]. We previously showed that successful CPAP treatment improved daytime baroreflex sensitivity and nitric oxide production in patients with moderate to severe OSA, hence CPAP may reduce the risk of cardiovascular complications due to endothelial dysfunction or increased sympathetic activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…When adherence is greater than 4 hours of nightly use, 46 to 83% of OSA patients were reported to be nonadherent to the treatment [13]. Increasing daily use of CPAP lowers blood pressure [10] and reduces the risk of incident stroke [11] and cardiovascular death [12]. Vascular endothelial dysfunction and structural vascular changes have been implicated as early mechanisms in the pathophysiology of hypertension and other forms of vascular disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…El tratamiento tiene como objetivo resolver los signos y síntomas de la enfermedad, normalizar la calidad de sueño, disminuir el índice de apnea-hipopnea por hora (IAH/h), reducir las consecuencias de enfermedades concomitantes y disminuir la desaturación de oxígeno (8). Además, se ha evidenciado que contribuye a mejorar la calidad de vida debido al buen desarrollo de las actividades de la vida diaria y, en el área de salud pública, al disminuir los costos directos e indirectos que esta enfermedad genera.…”
Section: Introductionunclassified